KONTEN PROMOSI ANEKA PRODUK PALA BERBASIS SOSIAL MEDIA BAGI KELOMPOK WANITA TANI CITA MANDIRI - Lathifah, Suci Siti; Widiastuti, Diana; Supratman, Lilis; Azizah, Briantine Siti Nur; Haritsa, Angel Aulia; Aqilah, Siti (LPPM Universitas Nusa Mandiri, 2024)
The ineffectiveness of word-of-mouth marketing techniques and the low ability of partners (Cita Mandiri Women Farmers Group) in utilising digital media have made nutmeg products not optimally marketed. The service activity aims to improve the ability of partners to create promotional content so that they can do marketing through social media. Service activities are carried out in three stages, namely 1) The preparation stage by conducting observations and identifying partner problems. 2) The implementation stage by conducting training and assistance in creating promotional content and online marketing techniques through social media. 3) Evaluation stage. Involving the Wanita Tani Cita Mandiri group in community service activities with structured training programmes, ongoing mentorship, and partnerships with online communities, this group can develop digital skills, create more creative promotional content, and expand their market reach. With the implementation of this solution, Wanita Tani Cita Mandiri can optimise the potential of social media as a marketing tool, increase their income, and overall make a positive contribution in the economic and social empowerment of the local community. In conclusion, through collaboration, training, and innovation, this group can make social media-based promotional activities a driving force to achieve economic independence and sustainability.